2011
DOI: 10.1155/2011/761958
|View full text |Cite
|
Sign up to set email alerts
|

Tai Chi Enhances the Effects of Endurance Training in the Rehabilitation of Elderly Patients with Chronic Heart Failure

Abstract: Purpose. To assess if Tai Chi added to endurance training (ET) is more effective than ET alone in improving exercise tolerance and quality of life (QOL) of elderly patients with chronic heart failure (CHF). Design. Sixty CHF patients, age 73.8 ± 6 years, M/F 51/9, were enlisted. Thirty pts were randomized to combined training (CT) performing Tai Chi +ET and 30 patients to ET (ET only). Methods. At baseline and after 12 weeks all patients underwent 6-minute walking test (6MWT), assessment of amino terminal prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
97
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(97 citation statements)
references
References 29 publications
0
97
0
Order By: Relevance
“…3,24,25 Many researchers have reported that TCQ might be beneficial for improving exercise tolerance in both healthy people and those with chronic diseases. [26][27][28][29][30] According to the results of the present review, TCQ appears to demonstrate a greater improvement in physical activity such as exercise tolerance than intervention without exercise training. However, it cannot be confirmed that TCQ are the better complementary treatments for physical activity in COPD rehabilitation than other exercise training forms.…”
Section: Discussionmentioning
confidence: 60%
“…3,24,25 Many researchers have reported that TCQ might be beneficial for improving exercise tolerance in both healthy people and those with chronic diseases. [26][27][28][29][30] According to the results of the present review, TCQ appears to demonstrate a greater improvement in physical activity such as exercise tolerance than intervention without exercise training. However, it cannot be confirmed that TCQ are the better complementary treatments for physical activity in COPD rehabilitation than other exercise training forms.…”
Section: Discussionmentioning
confidence: 60%
“…Regarding the type of Tai Chi, the Yang style was used in 10 of the 24 studies (2 cancer32 41; 3 OA31 36 44; 4 HF43 52 55 58 and 1 COPD42). Sun style Tai Chi was used in four OA studies23 33 37 38 and two COPD studies 56 57.…”
Section: Resultsmentioning
confidence: 99%
“…Usual care or waitlist control was the most common comparison group,22–24 33 35–37 39 40 42 52 53 56 57 followed by comparison to another exercise intervention programme 31 32 55 58. The effectiveness of Tai Chi was compared with that of educational programmes in four studies 38 43–45.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[150][151][152] Future work is needed, however, to better determine the benefits of alternative rehabilitation approaches, such as tai chi, on muscle strength and endurance in patients with HF.…”
Section: 149mentioning
confidence: 99%